2010
DOI: 10.1002/jat.1599
|View full text |Cite
|
Sign up to set email alerts
|

Protective actions of des‐aspartate‐angiotensin I in mice model of CEES‐induced lung intoxication

Abstract: The present study investigated the protective actions of des-aspartate-angiotensin I (DAA-I) in mice that were intranasally administered 2-chloroethyl ethyl sulfide (CEES), a half sulfur mustard. The protection was dose-dependent, and an oral dose of 75 mg kg⁻¹ per day administered 18 h post exposure and for the following 13 days, offered maximum protection that increased survival by a third. DAA-I attenuated the early processes of inflammation seen in the CEES-inoculated mice. DAA-I attenuated (i) elevated pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…The effect waned off within a week after cessation of DAA-I treatment. These findings are in agreement with those of earlier studies showing that the actions of DAA-I were losartan- and indomethacin-sensitive [ 7 , 8 , 11 , 13 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…The effect waned off within a week after cessation of DAA-I treatment. These findings are in agreement with those of earlier studies showing that the actions of DAA-I were losartan- and indomethacin-sensitive [ 7 , 8 , 11 , 13 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…59 CEES also causes pulmonary oxidative stress, characterized by increases in superoxide dismutase (SOD), Ym-1, and lipid peroxidation end products and decreases in intracellular glutathione levels. [60][61][62] Inflammatory proteins, including inducible nitric oxide synthase (iNOS), cyclooxygenase (COX)-2, TNFα, TNFR1, and CCR2 are also increased in the lung after CEES. 56,61,62 These responses are linked to functional alterations, including decreases in lung compliance and increases in elastance.…”
Section: Rodent Models Of Mustard Lung Injury Used To Investigate The...mentioning
confidence: 99%
“…Accordingly, DAA-I has been shown to be efficacious in animal models of cardiac hypertrophy [1], neointima formation [2], arteriosclerosis [2], renal failure [3], post-infarction injuries [4, 5], diabetes [6, 7], viral infection [8], chemical-induced inflammation [9], heat stroke [10], cancer [10] and gamma radiation lethality [11], where it has been found to significantly attenuate the severity of the pathology. At effective doses, DAA-I has no observable effects on the basal physiological and biochemical parameters that were measured in these studies and was found to lack secondary responses that could be considered adverse or side effects.…”
Section: Introductionmentioning
confidence: 99%